Host tracking or resource tracking? the case of Periglischrus wing mites (Acarina: Spinturnicidae) of leaf-nosed bats (Chiroptera: Phyllostomidae) from Michoacán, México. - Sheeler Gordon, Lorinda L.; D. Owen, Robert (Instituto de Ecología, A.C., 1999)
We examined the issue of host tracking versus resource tracking in spinturnicid wing mites of the genus Periglischrus, which are associated with bats of the family Phyllostomidae. Several lines of evidence suggest that these mites are host tracking, that is they do not respond to environmental factors beyond the body of their host. With one exception only, each host species was infested by only one mite species. In some cases, a mite species infested more than one bat species, but these hosts were always closely related, composing a monophyletic group within our sample. Finally, GIS analyses were used to evaluate the effects of annual precipitation, vegetation, climate, and soils on mite distributions within their host distributions in Michoacán. Those associations having an adequate sample size resulted in non-significance, indicating that the mite distributions did not vary with respect to environmental factors. Additional data and analyses are needed to test each of these findings, as well as to evaluate other environmental factors not tested in this study which may be of importance to mite distribution.